Abundance of Zooplankton in Striped Catfish (Pangasianodon sp) Culture on Feeding Fish Offal - Fajar Alfisyahrin; Syafriadiman Syafriadiman; Saberina Hasibuan (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2024)
The research was conducted from Agustus - September 2020 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study aims to determine the effect of feeding made from fish offal on the growth of catfish and the abundance of zooplankton. The method used was a completely randomized design experiment with one factor, five treatments, and three replications. The treatment used P0 = without giving fish offal pellets, P1 =25% of fish offal pellets, P2 = 50% of fish offal pellets, P3 = 75% of fish offal pellets, and P4 = 100% of fish offal pellets. Parameters observed were zooplankton abundance, diversity index, dominance index, specific growth rate, survival, and water quality. The results of the provision of fish offal pellets affected the abundance of zooplankton. The best treatment in this study was the P2 (50% fish offal pellets) with the results of zooplankton abundance of 6686 ind/L, a specific growth rate of 2.80%, a feed conversion ratio of 1.25, and survival rate of 83.33%. Water quality parameters during the research were classified as good, and the temperature was 28-29 0C, pH 6.7-7.0, DO 6.7-7.2 mg/L, and NH3 0.0022- 0.0045 mg/L.